Association of Clinical Pharmacist Interventions With Outcomes in Severe Diabetic Foot Infections: A Retrospective Cohort Study. - Wu, Ping; Ni, Chunyan; Sun, Xuemei; Xu, Wendong; Chauhan, Anjali (Journal of Clinical Pharmacy & Therapeutics, 2026)
Background: It is common for clinical pharmacists to participate in the management of antimicrobial therapy in many countries, but not all countries have clinical pharmacists participating in the antimicrobial treatment of patients with diabetic foot. Aim: To evaluate the effects of the involvement of clinical pharmacists in the management of severe infection in patients with diabetic foot. Method: A total of 89 patients with severe diabetic foot infection were enrolled in this retrospective study from January 2020 to December 2024, and they were divided into the study group (SG, n = 44) and the control group (CG, n = 45). Patients in the SG received clinical pharmacist intervention during hospitalization, while those in the CG received only general services. The Student′s t‐test and the Mann–Whitney U test were used for intergroup comparison of continuous variables, while the Chi‐square test was adopted for categorical variables. Results: No significant differences were identified between the SG and CG with respect to their sociodemographic or infection characteristics. The median duration of fever was shorter in the SG (3.00 days) than in the CG (6.00 days). After 3 days of antimicrobial treatment, the SG showed significantly larger decreases in the WBC count, C‐reactive protein (CRP), and procalcitonin (PCT) than the CG (p < 0.05). The SG had a significantly higher prevalence of appropriate initial empirical antimicrobial therapy (93.18% vs. 48.89%, p = 0.001), fewer drug‐related complications (13.64% vs. 51.11%, p < 0.001), and a lower prevalence of readmission over the first 12 months following discharge (2.27% vs. 17.78%, p = 0.030). The prevalence of antimicrobial regimen adjustments of ≥ 2 was also lower in the SG group (9.10% vs. 35.56%, p = 0.004). There were no significant differences in the prevalence of amputation or the defined daily dose between the groups. Conclusion: The involvement of clinical pharmacists in the management of severe infection in patients with diabetic foot was associated with improved acute infection control and the alleviation of drug‐related problems associated with antimicrobial agents, thereby providing a valuable reference for antimicrobial therapy management in such patients.